2021
DOI: 10.1038/s41598-021-84837-y
|View full text |Cite
|
Sign up to set email alerts
|

A gene module identification algorithm and its applications to identify gene modules and key genes of hepatocellular carcinoma

Abstract: To further improve the effect of gene modules identification, combining the Newman algorithm in community detection and K-means algorithm framework, a new method of gene module identification, GCNA-Kpca algorithm, was proposed. The core idea of the algorithm was to build a gene co-expression network (GCN) based on gene expression data firstly; Then the Newman algorithm was used to initially identify gene modules based on the topology of GCN, and the number of clusters and clustering centers were determined; Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…23 As a result of various studies, CCNB1 is believed to be overexpressed in HCC. 21,22,2430 However, a large sample size is needed to verify the expression patterns of CCNB1 in HCC, and the mechanisms of CCNB1 in HCC are still unknown. Moreover, the potential clinical implications of CCNB1 expression in HCC patients need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…23 As a result of various studies, CCNB1 is believed to be overexpressed in HCC. 21,22,2430 However, a large sample size is needed to verify the expression patterns of CCNB1 in HCC, and the mechanisms of CCNB1 in HCC are still unknown. Moreover, the potential clinical implications of CCNB1 expression in HCC patients need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…WGCNA has the advantage of computing complex network relationships but suffers from the disadvantage of ignoring modularity in module identification process and no flexibility to adjust the algorithm in the calculation. For the important role of modularity in network clustering and community detection, high modularity raising more reliable clustering results ( 62 ). Considering that WGCNA cannot identify modules with overlapping genes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NOP56 is significantly correlated with the survival prognosis, pathological stage, immune infiltration, and tumor progression of patients with hepatocellular carcinoma, and may be used as a target for the diagnosis and treatment of hepatocellular carcinoma in the future. The methylation analysis indicated that the hypomethylation of the NOP56 promoter may lead to the overexpression of NOP56, which proved that expression of NOP56 may be a potential biomarker of hepatocellular carcinoma (66,67). In hepatocellular carcinoma, NOP56 is considered as a potential immune marker associated with HBV virus, which can be processed and presented by antigenpresenting cells (APCs) to induce immune responses.…”
Section: Nop56 and Hepatocellular Carcinomamentioning
confidence: 99%